BRAINDEX: An Interactive, Knowledge-Based System Supporting Brain Death Diagnosis - Rom, G.; Schwarz, G.; Grims, R.; Rumpl, E.; Pfurtscheller, G.; Haase, V. (Methods of Information in Medicine, 1990)
BRAINDEX (Brain-Death Expert System) is an interactive, knowledge-based expert system offering support to physicians in decision making concerning brain death. The physician is given the possibility of communicating in almost natural language and, therefore, in terms with which he is familiar. This updated version of the system is implemented on an IBM-PC/AT with the expert system shell PC-PLUS and consists of about 430 rules. The determination of brain death is realized with backward chaining and for the optional coma-scaling a forward-chaining mechanism is used.
Keywords: Brain Death; Organ Transplantation; Rule-Based Expert System; Forward Chaining; Backward Chaining